2015
DOI: 10.1186/s12967-015-0656-0
|View full text |Cite
|
Sign up to set email alerts
|

STAT1 modification improves therapeutic effects of interferons on lung cancer cells

Abstract: BackgroundInterferons (IFNs) have potent anti-proliferative, pro-apoptotic, and immunomodulatory activities against cancer. However, the clinical utility of IFNs is limited by toxicity and pharmacokinetics making it difficult to achieve sustained therapeutic levels especially in solid tumors.MethodsSignal Transducer and Activator of Transcription 1 (STAT1) or a modified STAT1 (designated STAT1-CC) that is hyper-responsive to IFN were overexpressed in lung cancer SPC-A-1 and H1299 cells using lentiviral vectors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 41 publications
0
18
0
1
Order By: Relevance
“…4f-g, STAT1 and CD86 were negatively regulated by YTHDF1. Previous studies demonstrated that the loss of STAT1 activation or expression was found in malignant cells derived from various tumors, while the loss of CD86 expression resulted in a decrease in tumor-infiltrating T lymphocytes in diffuse B-cell large-cell lymphoma [30][31][32][33][34][35]. YTHDF1 Fig.…”
Section: Discussionmentioning
confidence: 99%
“…4f-g, STAT1 and CD86 were negatively regulated by YTHDF1. Previous studies demonstrated that the loss of STAT1 activation or expression was found in malignant cells derived from various tumors, while the loss of CD86 expression resulted in a decrease in tumor-infiltrating T lymphocytes in diffuse B-cell large-cell lymphoma [30][31][32][33][34][35]. YTHDF1 Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Because IKK⑀ directly phosphorylates STAT1 (36) and exerts antitumor activity (37,38), we investigated how fascin1 affects STAT1 phosphorylation in the IFN feedback loop. RIG-I facilitates the positive feedback loop of type I IFN production (39).…”
Section: Fascin1 Suppresses Rig-i Signalingmentioning
confidence: 99%
“…INS-1 cells were seeded into 96-well plates at a density well and preincubated for 24 h in an incubator at 37°C. Cell viability was assayed using a Cell Counting Kit-8 (CCK-8) assay kit (Dojin Laboratories, Kumamoto, Japan)according to the manufacturer's protocol(32).…”
mentioning
confidence: 99%